2020
DOI: 10.1186/s12951-020-00654-x
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine transporter-derived homing peptides enable rapid endocytosis of drug delivery nanovehicles into neuroblastoma cells

Abstract: Background: Currently, the diagnosis and treatment of neuroblastomas-the most frequent solid tumors in children-exploit the norepinephrine transporter (hNET) via radiolabeled norepinephrine analogs. We aim to develop a nanomedicine-based strategy towards precision therapy by targeting hNET cell-surface protein with hNET-derived homing peptides. Results: The peptides (seq. GASNGINAYL and SLWERLAYGI) were shown to bind high-resolution homology models of hNET in silico. In particular, one unique binding site has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…A previous ferritin study of a large sample of neuroblastoma patients found that ferritin had a strong impact on the prognosis of high-risk NB patients receiving modern treatment after 2009, and ferritin show promise for (1) identifying ultra-high-risk; (2) re ning risk strati cation; and (3) clinical utility in low-/middle-income countries [16]. In addition, ferritin plays an important role in peptide-based active delivery of nanomedicines to neuroblastoma cells [17] . This is consistent with the ndings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous ferritin study of a large sample of neuroblastoma patients found that ferritin had a strong impact on the prognosis of high-risk NB patients receiving modern treatment after 2009, and ferritin show promise for (1) identifying ultra-high-risk; (2) re ning risk strati cation; and (3) clinical utility in low-/middle-income countries [16]. In addition, ferritin plays an important role in peptide-based active delivery of nanomedicines to neuroblastoma cells [17] . This is consistent with the ndings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Label-free analysis of the effect of hMT3 up-regulation on proliferation of Huh7 cells was performed using real-time electrical impedance measurement on the xCELLigence RTCA DP instrument (Roche Diagnostics GmbH, Basel, Switzerland) according to a previous study [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Protein-based artificial nanosystem is another novel protein-based therapeutic with the requirement of high affinity. Yazan Haddad and co-workers developed an ellipticine-loaded ferritin with surface modification of the norepinephrine transporter (hNET) targeting peptides for tumor-targeting ability [188] . With computational methods, homology modeling, molecular docking, and molecular dynamics in this research, they found that these peptides showed an intriguing binding affinity with hNET.…”
Section: Computational Methods For the Rational Design Of Protein-bas...mentioning
confidence: 99%